2019
DOI: 10.1021/acs.analchem.9b02300
|View full text |Cite
|
Sign up to set email alerts
|

Single Chain Cationic Polymer Dot as a Fluorescent Probe for Cell Imaging and Selective Determination of Hepatocellular Carcinoma Cells

Abstract: This letter describes formation of single chain cationic polymer dots (Pdots) made of poly [1,4-dimethyl-1-(3-((2,4,5-trimethylthiophen-3yl)oxy)propyl)piperazin-1-ium bromide] conjugated polyelectrolyte (CPE). The single chain Pdot formation relies on a simple process which is a rapid nanophase separation between CPE solution of ethylene glycol and water. Pdots show narrow monodisperse size distribution with a 3.6 nm in diameter exhibiting high brightness and excellent colloidal and optical stability. It has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…In a related example, cationic single-chain Pdots were found to selectively accumulate in the nuclei of liver cancer cells but not in the nuclei of healthy liver cells. This effect enabled discrimination between the two populations in coculture and was attributed to altered nuclear membrane structure and larger pore size in the cancer cells …”
Section: Cellular Tissue and In Vivo Imaging And Theranosticsmentioning
confidence: 99%
“…In a related example, cationic single-chain Pdots were found to selectively accumulate in the nuclei of liver cancer cells but not in the nuclei of healthy liver cells. This effect enabled discrimination between the two populations in coculture and was attributed to altered nuclear membrane structure and larger pore size in the cancer cells …”
Section: Cellular Tissue and In Vivo Imaging And Theranosticsmentioning
confidence: 99%
“…A variety of liquid biopsy methods for liver cancer biomarkers have been developed, including electrochemical, [12][13][14][15][16] acoustics, 17 and fluorescence detection. [18][19][20][21][22][23] Although electrochemical detection excels in vastly reducing ambient interferences, it involves complicated procedures and therefore remains difficult to implement clinically. Chemiluminescence or bioluminescence detection suffers from suboptimal signal intensities and signal-tonoise ratios, leading to impaired detection capabilities.…”
Section: Introductionmentioning
confidence: 99%
“…Single chain polymer dots in reduced diameter (<10 nm) have shown improved quantum yield, photostability, and colloidal stability [21][22][23][24][25][26][27][28] as compared to larger diameter polymer dots. Recently, Ozenler et al demonstrated the use of single-chain polymer dots for differentiation of cancer and healthy cells in co-culture medium [29]. Though single chain polymer dots are expected to show unambiguous advantages in imaging, post-functionalization possibilities are still limited due to the small surface area.…”
Section: Introductionmentioning
confidence: 99%